New records of rare pierids (Lepidoptera: Pieridae) in Slovenia - Željko Predovnik; Rudi Verovnik (Natura Sloveniae)
The authors present new and unpublished information on the distribution of three pierid species in Slovenia, i.e. Gonepteryx cleopatra (Linnaeus, 1767), Colias erate (Esper, 1805), and Colias myrmidone (Esper, 1781). The first two species are very recent additions to the Slovene butterfly fauna and their status in view of the new records is discussed. Colias erate could be considered a resident species in Slovenia as it was found in two consecutive years on two sites along the Drava channels below Formin and Zlatoličje hydroelectric power plants. Colias myrmidone has suffered strong decline throughout the western limit of its distribution in central Europe and should be considered near extinct in Slovenia. The last records of this species in Slovenia are documented.